The Acquisition Order of Cohesion Connectives in Jordanian Spoken Arabic: A Contrastive Study - Kholoud Al-Rosan (International Journal of Social Sciences, Language and Linguistics, 2025)
The present study tries to investigate the acquisition order of cohesion connectives in Jordanian Spoken Arabic (JSA). Cohesion connectives are considered cognitive elements rather than merely discourse markers because they depend on cognitive and mental analysis (Spooren and Sanders, 2008). The study compares the results with their counterparts in English language, therefore, it is a contrastive study. In English, the acquisition order of cohesion relations has been examined by Bloom et al. (1980) who identified the order of acquiring the cohesion relations as follows: additive< temporal<causal< adversative. For example, and> and then< because<but. Moreover, the order shows that the more complex cohesion relations will be acquired later than simple relations. This order will be compared with the one at the end of the study. The study will focus on cohesion markers in JSA such as: wa (and)> ba؟dein (and then)> li?annu (because)> bas (but) and other coherence markers which will be extracted from the results.